Relationships Amongst Irrigation Facilities, Farmer’s Participation and Organizational Climate to Farming Goals - Kurniati, Evi; Rahadi, Bambang (Jurnal Teknologi Pertanian, 2000)
The greatest governmental investments to farming were irrigation facilities. Those were important to developed and built Indonesian farming. To preserved the conditions,it needed caring from everyone especially their user. It means that farmer’s participation,and user organizations were the most important thing. The research was conducted in Molek irrigated zone, on Kepanjen, Malang regency.Used three independent variables i.e. irrigation facilities, farmer’s participation, anduser organizational climate, and one dependent variable that was farming goals, thenanalyzed by statistics included validity and reliability test, correlation and linearregression. The result showed that irrigation facilities (X1), farmer’s participation (X), and userorganizational climate (X) had a positive correlation (direct relationship) with thefarming goals (Y), followed equation Y = 0.455 + 0.3322 X31 + 0.2845 X.Keyword: irrigation, farmer’s participation, and  organizational climate